Exploring Gopeng, perakas adventure tourism destination from tourist perspectives - Jamil, Nur Diyana Syahirah; Sawari, Siti Salwa (2019)
This study will be catered the current well-known product development in tourism field. The adventure tourism is one of the curious tourism products around the people. Additionally, there are various people’s preferences appoint to adventure tourism. Indeed, this target market can keep it on to purchase the adventure tourism product regarding to its safety performances. Within there have a lots of promoted activities in adventure tourism, the research eager to know more on how this product influences tourist’s perspectives. Hence, this study appointed three main objectives which are to identify the motives of tourist when purchasing the adventure tourism packages, to investigate the safety performances from the tourist perspectives and to analyse the factors of adventure tourism influences the tourist perspectives. Basically, the methodology of this research will embark in descriptive analysis which dependably using various article to support the points. On the other hand, the findings also will be created based on the scholar, other research and so on to firm the majority of results. This study resulted in three main components which are perceived severity aspect, non-routine living norms and nature factors.